Randomized Trial Comparing Resection of Primary Tumor With No Surgery in Stage Iv Breast Cancer at Presentation: Protocol Mf07-01 - Soran, Atilla; Sezgin, Efe; Özmen, Vahit; Özbaş, Serdar; Karanlık, Hasan; Müslümanoğlu, Mahmut; İgci, Abdullah; Johnson, Ronald; Sezgin, Efe (Springer, 2018)
The MF07-01 trial is a multicenter, phase III, randomized, controlled study comparing locoregional treatment (LRT) followed by systemic therapy (ST) with ST alone for treatment-na < ve stage IV breast cancer (BC) patients. At initial diagnosis, patients were randomized 1:1 to either the LRT or ST group. All the patients were given ST either immediately after randomization or after surgical resection of the intact primary tumor. The trial enrolled 274 patients: 138 in the LRT group and 136 in the ST group. Hazard of death was 34% lower in the LRT group than in the ST group (hazard ratio [HR], 0.66; 95% confidence interval [CI], 0.49-0.88; p = 0.005). Unplanned subgroup analyses showed that the risk of death was statistically lower in the LRT group than in the ST group with respect to estrogen receptor (ER)/progesterone receptor (PR)(+) (HR 0.64; 95% CI 0.46-0.91; p = 0.01), human epidermal growth factor 2 (HER2)/neu(-) (HR 0.64; 95% CI 0.45-0.91; p = 0.01), patients younger than 55 years (HR 0.57; 95% CI 0.38-0.86; p = 0.007), and patients with solitary bone-only metastases (HR 0.47; 95% CI 0.23-0.98; p = 0.04). In the current trial, improvement in 36-month survival was not observed with upfront surgery for stage IV breast cancer patients. However, a longer follow-up study (median, 40 months) showed statistically significant improvement in median survival. When locoregional treatment in de novo stage IV BC is discussed with the patient as an option, practitioners must consider age, performance status, comorbidities, tumor type, and metastatic disease burden.